Respostas
respondido por:
7
→ (2p -1)x² - 2px - 2 = 0
Como 2 é raiz da equação, substitua no lugar do x:
(2p -1)2² - 2p2 - 2 = 0
(2p - 1)4 -4p -2 = 0
8p -4 -4p - 2 = 0
4p - 6 = 0
4p = 6
p = 6/4 = 3/2 (De forma simplificada)
Espero que tenha ajudado,
Como 2 é raiz da equação, substitua no lugar do x:
(2p -1)2² - 2p2 - 2 = 0
(2p - 1)4 -4p -2 = 0
8p -4 -4p - 2 = 0
4p - 6 = 0
4p = 6
p = 6/4 = 3/2 (De forma simplificada)
Espero que tenha ajudado,
brendhakawany1:
Obrigada!!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás